Novel imaging findings in pyruvate dehydrogenase complex (PDHc) deficiency—Results from a nationwide population‐based study. Issue 2 (17th December 2021) - Savvidou, Antri; Ivarsson, Liz; Naess, Karin; Eklund, Erik A.; Lundgren, Johan; Dahlin, Maria; Frithiof, Deborah; Sofou, Kalliopi; Darin, Niklas
Abstract: The vast clinical and radiological spectrum of pyruvate dehydrogenase complex (PDHc) deficiency continues to pose challenges both in diagnostics and disease monitoring. Prompt diagnosis is important to enable early initiation of ketogenic diet. The patients were recruited from an ongoing population‐based study in Sweden. All patients with a genetically confirmed diagnosis who had been investigated with an MRI of the brain were included. Repeated investigations were assessed to study the evolution of the MRI changes. Sixty‐two MRI investigations had been performed in 34 patients (23 females). The genetic cause was mutations in PDHA1 in 29, PDHX and DLAT in 2 each, and PDHB in 1. The lesions were prenatal developmental in 16, prenatal clastic in 18, and postnatal clastic in 15 individuals. Leigh‐like lesions with predominant involvement of globus pallidus were present in 12, while leukoencephalopathy was present in 6 and stroke‐like lesions in 3 individuals. A combination of prenatal developmental and clastic lesions was present in 15 individuals. In addition, one male with PDHA1 also had postnatal clastic lesions. The most common lesions found in our study were agenesis or hypoplasia of corpus callosum, ventriculomegaly, or Leigh‐like lesions. Furthermore, we describe a broad spectrum of other MRI changes that include leukoencephalopathy and stroke‐like lesions. We argue that a novel important clue, suggesting the possibility of PDHc deficiency on MRI scans, is the simultaneous presence of multiple lesions on MRI that have occurred during different phases of brain development.